Surviving the 2015 Mount Everest disaster: A phenomenological exploration into lived experience and the role of mental toughness. (November 2016) - Swann, Christian; Crust, Lee; Allen-Collinson, Jacquelyn
Abstract: Objectives: The 2015 Nepal earthquake and subsequent avalanche at Mount Everest Base Camp is the deadliest mountaineering disaster to date. This study is novel in exploring the lived experiences of survivors and the role of mental toughness in their psychological responses to the disaster. Design: Phenomenological study. Method: Ten mountaineers, who were on expeditions during the earthquake, participated in phenomenological interviews. Data were analysed inductively and thematically, while strategies to enhance trustworthiness were also employed. Results: Seven dimensions emerged from the data, which captured climbers' psychological responses to the disaster, ranging from the moments the earthquake hit to reflections on the disaster after returning home. Contrasting emotional responses were described, and suggested to depend on experience and mental toughness. Negative emotional and behavioural responses were reported in the aftermath. Some climbers reported post-traumatic stress, but also a strong desire to return to Mount Everest and continue mountaineering. Conclusions: These findings provide detailed insights into the lived experiences of climbers who survived the 2015 Nepal earthquake and Base Camp avalanche. Findings also shed light on the role of mental toughness in coping with and responding to a major natural disaster. Highlights: Phenomenological interviews were conducted with 10 high-altitude mountaineers. Participants were on Everest during the 2015 earthquake and Base Camp avalanche. Interviews explored the role of mental toughness in emotional and coping responses. Findings provide insight into survivors' lived experiences of this natural disaster.